Menopausal symptoms and the awareness of menopausal-related information in low-income mid-aged women from Guayaquil, Ecuador - Danny Salazar-Pousada; Valeria Ortega-Uscocovich; Cecibel Ramírez-Morán; Peter Chedraui (Gynecological Endocrinology)
Objective To assess menopausal symptoms and determine awareness of menopausal related information in mid-aged women.Methods This was a cross-sectional study in which 140 women aged 40 to 60 years from Guayaquil, Ecuador were surveyed with the short 10-item Cervantes Scale (CS-10) and a questionnaire containing personal data and questions assessing awareness of menopause related information.Results The mean age of the sample was 48.0 ± 5.6 years. More than half of surveyed women had low education and non-urban residency, none were on menopausal hormone therapy, 33.6% had hypertension, 35% were postmenopausal, 78.6% had an increased body mass index (overweight/obese) and 92.9% had abdominal obesity (waist > 88 cm). The average CS-10 score was 15.3 ± 9.0 with a median of 14.0. The three most frequent menopausal symptoms were muscle-joint pain (75.0%), changes in skin texture (74.3%) and vaginal dryness (71.4%). Regarding awareness of information related to the menopause, it was found that 98.6% of women had no idea about what the menopause is and the average age of its onset. Interestingly, although 61.4% knew that during the menopause there is weight gain, 57.9% were sedentary. Married, postmenopausal, older and less educated women presented higher mean total CS-10 scores. Contrarily, those with less awareness of menopause related information present lower scores.Conclusion In this low-income mid-aged female sample there was a high rate of non-awareness regarding information related to the menopause, including an unhealthy cardiometabolic profile. There is a need for educational programs aimed to increase awareness in this high-risk population in relation to the surveyed aspects in order to improve their health status and prevent chronic conditions.